Assessing The Impact of Environmental Climate Change On Malaysia Economic Performance - Lee, Wei Jie (Universiti Malaysia Sarawak (UNIMAS), 2020)
The impact of environmental climate change has become more significant recently. Environmental climate change able to bring negative impacts that might affect the economy of a country, including Malaysia. The purpose of this study is to determine the relationship between environmental climate change and economic performance from the macroeconomic perspective in Malaysia by using time series analysis from year 1975 to year 2019. Real Gross Domestic Product (RGDP) will be the dependent variable in this study. The independent variables in this study included carbon dioxide emission, rainfall and government expenditure. Vector Error-Correction Model (VECM) approach was developed to identify the short-run causality and log-run relationship between those variables. The result of this study showed that environmental-climate factors have a positive impact on Malaysia's economy and Environmental Kurznet Curve(EKC) hypothesis is valid in this study. Although there is a positive impact between environmental-climate factors and Malaysia's economy, the government should focus more on the environmental climate change issue before it negatively impacts the economy in Malaysia.